Operation support system blue print and evolution strategy for SDN/NFV - Yanbin SHI; Qi YU; Xiaojun XIE (Dianxin kexue)
Firstly,the challenges of operation support system for SDN / NFV were described,such as agile efficient processes,real-time on-demand service,and hybrid network.Secondly,the industry trends of international operators and standard organizations were introduced,and the current situation of operation support system was analyzed,inluding the capability,the interconnection and the automation.Lastly,the new generation of intelligent,efficient,flexible and open operation support system implementation blue print,boundary division and evolution strategy were proposed.